The Effect of Fundamental Factor Analysis on Blue Chips Stock Returns on the Indonesia Stock Exchange - Putri Rosarindah Lubis (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to determine the effect of fundamental analysis consisting of price earning ratio, net profit margin, price to book value, return on equity, debt to equity ratio, and dividend payout ratio on stock returns on blue chips on the Indonesia Stock Exchange. The research method used is multiple linear regression analysis method, and hypothesis testing is done by testing the significance of the effect simultaneously (simultaneously) using the F-test and testing the significance of the partial effect using the t-test. This study uses secondary data in the form of financial statements of companies listed in blue chips on the Indonesia Stock Exchange in 2005–2007. The results showed that simultaneously (simultaneously) operational effectiveness (price earning ratio, net profit margin, price to book value, return on equity, debt to equity ratio, and dividend payout ratio) have a significant effect on stock returns. Partially there is a negative and significant effect between the price earning ratio on stock returns. Partially there is no significant effect between net profit margin on stock returns. Partially there is no significant effect between price to book value on stock returns. Partially there is a positive and significant effect between return on equity on stock returns. Partially there is a positive and significant effect between debt to equity ratio on stock returns. Partially there is a positive and significant effect between the dividend payout ratio on stock returns.